2020
DOI: 10.1016/j.abd.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on the diagnosis and management of chronic leg ulcers - Brazilian Society of Dermatology

Abstract: Background Chronic leg ulcers affect a large portion of the adult population and cause a significant social and economic impact, related to outpatient and hospital care, absence from work, social security expenses, and reduced quality of life. The correct diagnosis and therapeutic approach are essential for a favorable evolution. Objective To gather the experience of Brazilian dermatologists, reviewing the specialized literature to prepare recommendations for the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 79 publications
1
29
0
19
Order By: Relevance
“…11 The treatment of VLUs consisted of measures to reduce the effects of venous hypertension (compression therapy, surgical treatment for venous abnormality), local treatment for the ulcer, systemic drugs, and complementary measures (leg elevated above the level of the heart, short walks). 12 Compression therapy remains as the first-line and standard treatment for VLUs, which in turn improves venous hemodynamics by applying external pressure to the ankle around 35–40 mmHg. 12 The lifelong maintenance of compression therapy is necessary to decrease the risk of ulcer recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The treatment of VLUs consisted of measures to reduce the effects of venous hypertension (compression therapy, surgical treatment for venous abnormality), local treatment for the ulcer, systemic drugs, and complementary measures (leg elevated above the level of the heart, short walks). 12 Compression therapy remains as the first-line and standard treatment for VLUs, which in turn improves venous hemodynamics by applying external pressure to the ankle around 35–40 mmHg. 12 The lifelong maintenance of compression therapy is necessary to decrease the risk of ulcer recurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Compression therapy remains as the first-line and standard treatment for VLUs, which in turn improves venous hemodynamics by applying external pressure to the ankle around 35–40 mmHg. 12 The lifelong maintenance of compression therapy is necessary to decrease the risk of ulcer recurrence. 13 Meanwhile, for cases of VLUs associated with KS, there is no established therapy.…”
Section: Discussionmentioning
confidence: 99%
“…12 Therapeutic options for CPUL start with prevention, such as daily inspection of the feet, cleaning and drying of the interdigital, straight nail cutting, hydration, callus removal, examinations of the deformities of the feet, and others. 13 However, in patients with CPUL already ongoing, the approach must be multidisciplinary. Other than the standardized leprosy chemotherapy, novel treatment such as applying Stem Cells (SC) could be an option as described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of EVs in wound healing has shown that MSC-derived EVs play a significant role in hemostasis by controlling anti-inflammatory processes, proliferation, and remodeling [ 98 , 99 , 100 ]. In clinical trial NCT02565264, the researchers are studying the effect of plasma-derived EVs on intractable cutaneous ulcers, which are common manifestations in peripheral arterial disease, rheumatic disease, burns, decubitus, and chronic venous insufficiency [ 101 ]. Dystrophic epidermolysis bullosa (DEB) is a genetic disorder marked by the mutation in COL7A1 gene and manifested by abnormal blistering of limb skin.…”
Section: Clinical Trials Evaluating Peripherally Targeted Extracellul...mentioning
confidence: 99%